Safety and efficacy of using cereal food (Frugra®) to improve blood pressure and bowel health in patients undergoing chronic hemodialysis: A pilot study - Hajime Nagasawa; Seiji Ueda; Tomoyuki Otsuka; Kumiko Kaifu; Shigeo Ono; Teruyuki Okuma; Takashi Kobayashi; Satoshi Matsushita; Takatoshi Kasai; Tomotaka Dohi; Yoshifumi Fukushima; Atsushi Amano; et al. (Elsevier, 2021)
Hypertension and constipation are major hemodialysis complications. Salt restriction is one of the most important nonpharmacological interventions in managing hypertension. In patients undergoing hemodialysis, nonpharmacological strategies to manage constipation are extremely difficult to develop owing to the presence of excess dietary potassium and fluids. Frugra®, which is a cereal food that has a low salt content of 0.5 g per serving, may help reduce salt intake. Additionally, Frugra is rich in dietary fiber, thereby beneficial for such patients. In this study, we evaluated the safety and efficacy of Frugra in patients undergoing hemodialysis, focusing mainly on blood pressure and bowel health by changing the usual breakfast meal to Frugra for 8 weeks. We enrolled 11 patients undergoing hemodialysis. Despite the absence of changes in the patients' dry weight levels, their systolic blood pressure levels decreased from 155.5 ± 20.9 mmHg to 137.9 ± 10.3 mmHg after 2 months (P < 0.05). All participants reported improvements in bowel movement, and the levels of indoxyl sulfate, a representative gut-derived uremic toxin, were decreased from 49.3 μg/ml to 33.4 μg/ml. Furthermore, adverse events including electrolyte abnormalities were not observed. Therefore, Frugra may be useful to manage the health of patients undergoing hemodialysis.